(untitled) (International journal of artificial intelligence, 2026)
The integration of Artificial Intelligence into education has significantly influenced the way students develop academic writing skills, particularly in English as a Foreign Language (EFL) contexts. This study explores the impact of AI-based tools on the academic writing performance of EFL learners. The research aims to examine how applications such as ChatGPT, Grammarly, and other digital assistants affect students’ grammar accuracy, vocabulary use, organization of ideas, and overall writing quality. A mixed-method approach was employed, including questionnaires and comparative analysis of student writing samples produced with and without AI support. The findings indicate that AI tools contribute positively to improving language accuracy and writing efficiency. However, the study also reveals potential drawbacks, such as reduced critical thinking, creativity, and originality due to overdependence on AI. The paper concludes that while Artificial Intelligence can serve as a helpful educational resource, its use in academic writing should be balanced and guided to ensure effective learning outcomes.